1980
DOI: 10.1088/0029-5515/20/3/001
|View full text |Cite
|
Sign up to set email alerts
|

A study of quasi-mode parametric excitations in lower-hybrid heating of tokamak plasmas

Abstract: A detailed linear and nonlinear analysis of quasimode parametric excitations relevant to experiments in supplementary heating of tokamak plasmas is presented. The linear analysis includes the full ion-cyclotron harmonic quasimode spectrum. The nonlinear analysis, considering depletion of the pump electric field, is applied to the recent Alcator A heating experiment. Because of the very different characteristics of a tokamak plasma near the wall (in the shadow of the limiter) and inside, t-he quasimode excitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1980
1980
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Also, k 21 as given in Eq. 3 formulate the parametric decay assuming that the low frequency mode is non-resonant (i.e., it is a quasi-mode) (2]. This means that the wavenumber of the low frequency quasi-mode is to be chosen at any point in the plasma such that it matches the wavenumbers of the lower-hybrid waves.…”
Section: Results and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, k 21 as given in Eq. 3 formulate the parametric decay assuming that the low frequency mode is non-resonant (i.e., it is a quasi-mode) (2]. This means that the wavenumber of the low frequency quasi-mode is to be chosen at any point in the plasma such that it matches the wavenumbers of the lower-hybrid waves.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…where E 0 is the constant pump electric field which is related to ao as, Eoao, 2 the coordinates that lie respectively along and perpendicular to the pump propagation cone. We define a new coordinate system as,…”
Section: The Maximum Amplification Factormentioning
confidence: 99%
“…The linear theory of various parametric processes at the lower hybrid frequency range is well explored [2], and it predicts roughly the same density limit for their existence as experimental observations do. A detailed comparison with the theory and the experiment, recently made for the Alcator lower hybrid experiments [3,4], emphasizes the importance of a precise knowledge of density and temperature profiles as well as of wavenumber and frequency spectra of pump and decay waves in evaluating the role of parametric decay upon pump wave penetration. In addition, various non-linear mechanisms may modify the linear growth of parametric instabilities.…”
Section: Introductionmentioning
confidence: 93%
“…The spatial growth factor A has been calculted in Ref. [4] for a variety of tokamak parameters and for a broad spectrum of Ej. It was found that A is large at the edge of the plasma, and the excited spectrum has a frequency very close to the initial pump frequency, while the wavenumber spectrum may be very different from the initial linear spectrum (i.e.…”
Section: J P (/Px)j P + 1 (/Px)j 2 P + 1 (2/px)]} (17)mentioning
confidence: 99%
See 1 more Smart Citation